2018
DOI: 10.21037/atm.2017.11.34
|View full text |Cite
|
Sign up to set email alerts
|

Treating ALK-positive non-small cell lung cancer

Abstract: Targeting genomic alterations, such as epidermal growth factor receptor (EGFR) mutations and anaplastic lymphoma kinase (ALK) gene rearrangements, have radically changed the treatment of patients with non-small cell lung cancer (NSCLC). In the case of ALK-rearranged gene, subsequent rapid development of effective genotype-directed therapies with ALK tyrosine kinase inhibitors (TKIs) triggered major advances in the personalized molecularly based approach of NSCLC. Crizotinib was the first-in-class ALK TKI with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 92 publications
0
18
0
Order By: Relevance
“…Although a significant benefit can be achieved in the management of ALK -positive NSCLC with crizotinib, it is worth noting that a substantial risk of central nervous system (CNS) progression inevitably exists (13, 29). The patients with ALK -positive NSCLC have a high risk of developing CNS metastasis, as observed in ~30% of cases at the time of tumor diagnosis and in 50–60% of patients during crizotinib treatment (30). Our study analyzed brain metastases and progression pattern and found that brain metastases occurred in 32.7% of patients (34 of 104) with PD at the time of data cutoff during crizotinib therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Although a significant benefit can be achieved in the management of ALK -positive NSCLC with crizotinib, it is worth noting that a substantial risk of central nervous system (CNS) progression inevitably exists (13, 29). The patients with ALK -positive NSCLC have a high risk of developing CNS metastasis, as observed in ~30% of cases at the time of tumor diagnosis and in 50–60% of patients during crizotinib treatment (30). Our study analyzed brain metastases and progression pattern and found that brain metastases occurred in 32.7% of patients (34 of 104) with PD at the time of data cutoff during crizotinib therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Rearrangements of ALK gene accounts for approximately 3–7% of NSCLC patients with higher rates observed in younger, never or light smokers of adenocarcinoma [4]. Rapid development of targeted therapies for advanced ALK rearranged NSCLCs have shown higher response and longer response duration than cytotoxic chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 3–7% of patients with NSCLC have ALK rearrangement [4]. Targeted therapy for advanced ALK rearranged NSCLC have been developed and show a higher response and longer response duration than cytotoxic chemotherapy, by the first-generation ALK inhibitor, crizotinib and the second-generation, alectinib and ceritinib.…”
Section: Introductionmentioning
confidence: 99%
“…This particular translocation leads to oncogenic transformation of the cell through a constitutively active ALK kinase and can be effectively targeted through the available tyrosine kinase inhibitors (TKI). Despite a greater efficacy of targeted ALK inhibitorscompared with standard chemotherapy, development of acquired resistance is often a matter of time and disease progression is imminent 4. Therefore, identification of resistance mechanisms after targeted inhibition of the EML4-ALK fusion oncogene is crucial for designing an effective sequential treatment strategy.…”
Section: Introductionmentioning
confidence: 99%